Phytophthora austrocedri elicitates changes in diterpene profile of austrocedrus chilensis - Olate, Verónica Rachel (2015)
The populations of the Andean Cupressaceae Austrocedrus chilensis have been severely affected by a disease caused by the phytopathogenic fungus Phytophthora austrocedri. A study was undertaken to disclose changes in the resin composition of P. austrocedri-infected individuals, including naturally infected and artificially inoculated trees, compared with healthy A. chilensis trees. GC-MS and 1H-NMR studies showed a clear differentiation among healthy and infected resins, with the diterpene isopimara-8(9),15-dien-19-ol as a relevant constituent in resins from infected trees. The effect of resin fractions from P. austrocedri infected trees on the pathogen was assessed by measuring the mycelial growth in agar plates. The most active fractions from resin obtained from infected trees inhibited fungal growth by nearly 50% at 1 mg/dish (35.37 μg/cm2). The main constituent in the active fractions were 18-hydroxymanool and the aldehyde torulosal. Both compounds are oxidation products of manool and can be a chemical response of the tree to the pathogen or be formed from the pathogen as a biotransformation product of manool by microbial oxidation. While the diterpene profiles from A. chilensis tree resins can easily differentiate healthy and P. austrocedri infected individuals, the possible conversion of manool to the antifungal derivatives 4 and 6 by the microorganism remains to be established.